THE IMPACT OF MANAGING SUSTAINABLE EVENT AND THE CONTRIBUTION TO THE FORMATION OF DESTINATION IMAGE AT NUSA DUA RESORT, BALI - Komang Trisna Pratiwi Arcana; Kadek Wiweka (Institut Pariwisata dan Bisnis Internasional, 2015)
Â Nusa Dua Resort under management of BTDC (Bai Tourism Development Corporation) Nusa Dua Bali becomes an attractive tourist area in Bali and as one of MICE tourism destination in the world. The growth of MICE Tourism Industry also can cause the risk of long term sustainability of the development. Hence it is necessary to incorporate the principles of sustainability in the management of the event as part of the tourism industry through the implementation of Sustainable Event Management Concept. This research used qualitative method according to the social phenomenon at Nusa Dua Resort regarding the development of MICE tourism in that region. Nusa Dua Resort has MICE destination attributes to accommodate both of national and international scale event in term of: (i) accessibility; (ii) attraction; (iii) amenities and affordability; (iv) ancillary service; (v) special intermediaries; (vi) stakeholder support. Meanwhile implementation of Sustainable Event Management concept that demonstrated by PCO, DMC, and MICE Managementâ€™s team in Nusa Dua Resort subsequently derived some impacts for local community and creates an image to the business traveler whose use the product itself.